IMPLEMENTASI DANA BANTUAN OPERASIONAL SEKOLAH DI SMP NEGERI 3 PRACIMANTORO - indra, satrio (Jurnal Informasi dan Komunikasi Administrasi Perkantoran, 2014)
ABSTRACT The purpose of this research are (1) to find out the implementation of School Operational Grant in SMP Negeri 3 Pracimantoro in the school year of 2013/2014; (2) to understand the factors affecting the effectiveness of the implementation of School Operational Grant in SMP Negeri 3 Pracimantoro in the school year of 2013/2014; (3) to identify constraints and problems faced in the implementation of School Operational Grant in SMP Negeri 3 Pracimantoro in the school year of 2013/2014; and (4) to find out the solution to the problems in the implementation of School Operational Grant in SMP Negeri 3 Pracimantoro in the school year of 2013/2014.Considering the result of research, the following conclusions could be drawn. (1) In the implementation of School Operational Grant in SMP Negeri 3 Pracimantoro, there were some procedures taken by the school: planning, acting, supervising, evaluating, and reporting. (2) The Factors affecting the effectiveness of the implementation of School Operational Grant in SMP Negeri 3 Pracimantoro referred to the School Budget and Expenditure Income Budget (RAPBS) and BOS Technical Instruction (Juknis). (3) The constraints faced in the implementation of School Operational Grant in SMP Negeri 3 Pracimantoro included internal and external ones. Internal constraints included: a) employee expenditure was limited to maximum 20% of total BOS revenue; b) many student activities funded by BOS so that the fund had not been adequate yet; c) BOS supplementary fund revenue has not been adequate for a year need; d) The activities to improve the quality of teacher such as short course, workshop, technical guide, seminar and BOS fund allocation had not been adequate. The external constraints included: a) Building and road maintenance costs were very high because of labile geographical condition; b) weak social economic condition of parents; c) inadequate learning supporting media in classroom; d) low output of National Standardized Semester Final Examination Score for Elementary School. (4) The solution to deal with the problems in the implementation of School Operational Grant in SMP Negeri 3 Pracimantoro consisted of the solution for internal and the one for external constraints. Solutions to internal constraints were: a) percentage employee expenditure in BOS program should be increased; b) the school was allowed to receive voluntary contribution from students? parent; c) BOS supplementary fund was increased; d) the activity of improving the teacher quality was limited to or funded with personal fund from the teacher. The solution to external constraints included: a) DAK or blockgrant was required annually; b) the government should open job opportunities and provide productive economic improvement for the poor; c) there should be a special fund aid for procuring the learning media in classroom; d) there should be an improvement of education quality at Elementary School level.Keywords: Implementation, School Operational Grant